LITERASI KEUANGAN DAN PENGENALAN FINTECH UNTUK GENERASI MILENIAL PADA SISWA/I SMK BATAM INTERNATIONAL SCHOOL - Mortigor Afrizal Purba (Asosiasi Dosen Akutansi Indonesia, KEPRI, 2022)
Indonesian people's awareness of the importance of financial literacy is currently still low, especially in the millennial generation who are known to tend to be consumptive and do not have good financial management. In terms of financial planning and management, millennials have the characteristics of not saving/investing much, they prefer to seek experiences through traveling, buying gadgets, and expressing themselves through social media. So that the problems of the next millennial generation that will arise are spending that is greater than income, increasing loans and not being able to have a place to live because of unbalanced income and home mortgage costs. This makes it important to provide guidance on financial planning and management education for the millennial generation as mandated by the government through the Financial Services Authority. In addition, there is a need for an introduction to financial technology (fintech) for the millennial generation, because of the proximity of this generation to technology and practical principles. Fintech is one of the solutions in providing education and understanding of integrated financial products, as well as providing access for millennials to find out which financial planning products suit their needs. The target of this service is students or students of SMK Batam International School class 12 majoring in Accounting and Financial Institutions. This coaching was carried out on Friday and Saturday, February 15-16, 2019 at the Batam International School Vocational School, which is located at Rananta Shopping Complex Blok A No. 5-7 Legenda, Baloi, Batam Centre. The training participants were 18th graders majoring in Accounting and Informatics Engineering. Coaching is provided with methods of providing practical materials, concepts and tricks in preparing good finances, making financial plans/priorities in the future, and getting to know financial technology facilities that are easy to use today. The training participants were very enthusiastic because in addition to the material topics according to their majors, each training session was also provided with interesting games.